Genome-Wide Scanning Enabled SNP Discovery, Linkage Disequilibrium Patterns and Population Structure in a Panel of Fonio (Digitaria exilis [Kippist] Stapf) Germplasm - Ibrahim Bio Yerima, Abdou R.; Issoufou, Kassari Ango; Adje, Charlotte A.; Mamadou, Aissata; Oselebe, Happiness; Gueye, Mame Codou; Billot, Claire; Achigan-Dako, Enoch G. (Frontiers in Sustainable Food Systems, 2021)
White fonio (Digitaria exilis) is a staple food for millions of people in arid and semi-arid areas of West Africa. Knowledge about nutritional and health benefits, insights into morphological diversity, and the recent development of genomic resources call for a better understanding of the genetic structure of the extant germplasm gathered throughout the region in order to set up a robust breeding program. In this study, we investigated the genetic diversity and population structure of two hundred and fifty-nine fonio individuals collected from six West African countries (Benin, Burkina Faso, Guinea, Mali, Niger, and Nigeria) using 21,324 DarTseq-derived SNP markers. The results revealed a moderate level of genetic diversity probably due to the inbreeding and small population size. Furthermore, two clusters were found irrespective of the geographic origins of accessions. Moreover, the high level of linkage disequilibrium (LD) between loci observed resulted from the mating system of the crop, which is often associated with a low recombination rate. These findings fill the gaps about the molecular diversity and genetic structure of the white fonio germplasm in West Africa. This was required for the application of genomic tools that can potentially speed up the genetic gain in fonio millet breeding for complex traits such as yield, and other nutrient contents.